The Turkish State's Attitude Towards the Kurdistan Region: Descriptive – Analytical Research (Raparin Journal of Humanities (RJH), 2025)
After the fall of the Ottoman Empire, the Kurds territory were divided into four states. A large part of Kurdistan territory was annexed to the newly established Turkish state (1923). In terms of geopolitics, the Turkish state has always seen this part of Kurdistan as a threat to the security and identity of the state.This study aims to explain why the Kurdistan Region has been seen as an important place by Turkey since its establishment and has formed a major factor in Ankara's foreign policy, whether in the context of Turkey's policy towards Iraq or Turkey's special policy towards the Kurdistan Region. For this purpose, in addition to the relations between Turkey and the Kurdistan Region, the Turkish state's attitude towards the Kurdistan Region has been analyzed from the perspective of the constitution, official statements of the state and the political elite.Since the establishment of the new Republic of Turkey, until the 1990s, Ankara's approach to Iraq has treated the Iraqi Kurds as a threat to the security and identity of the state. Then the formation of power made Turkey look at the Kurdistan Region from a security and military perspective, this view continued until the years (2007-2008), but after this the Kurdistan Region was able to become the largest economic market for Turkey. The content of the research is analyzed within three themes: first, the identity of the Turkish state, second, the Turkish state's view of the Kurds as a nation in general and third, Turkey's view of the Kurdistan Region.